Ascending Danger in Childhood Intoxication: Amitriptyline - Genç, Gürkan; Saraç, Avni; Ertan, Ülker; Yüksel, Süer; Yüksek, Mutlu (Fırat University, 2007)
Objective: Amitriptyline intoxication rates within recent years show an increase in childhood intoxication, either by accidentally or by suicide attempt. In this study, increase observed in morbidity and mortality rates after Amitriptyline intake will be considered and precautions that need to be taken will be discussed. Materials and Methods: Records of the patients with amitriptyline intoxication diagnosis that have been hospitalized and pursued reviewed retrospectively in terms of age, gender, symptoms, clinical diagnosis, intensive care requirement, duration of hospitalization and the results. Results: 7,84% (n=61) of the 778 intoxication cases was with Amitriptyline either solely or together with others as multi-drug intoxications. 56,8% (n=29) of the cases were male and 43,2% (n=22) were female intoxicated with only Amitriptyline. The ages of the cases were between 13 months and 15 years. 76,4% (n=39) of the cases was accidental where 15,3% (n=8) of those was suicide attempt and 7,8% (n=4) was misuse. The most frequent application symptom was vomiting together with loss of consciousness with a percentage of 29,4% (n=15) and 23,5% (n=12) respectively. 27.4% (n=14) of the patients were asymptomatic. Hospitalization periods were between 1 and 20 days (average:3,6) 3 of the patients were died during treatment while the rest were recovered and discharged without any complication. Conclusion: Amitriptyline intoxication cases in childhood have been increasing during the study period. As there can be critical consequences, such as morbidity and mortality, preventive precautions become more important. ©2007, Firat University, Medical Faculty

Amaç: Çocukluk çağı zehirlenmelerinin gerek kaza sonucu gerekse intihar amaçlı zehirlenmelerinde amitriptilin intoksikasyonları sayısı gün geçtikçe artış göstermektedir. Bu çalışmada, amitriptilin alımı sonrası morbidite ve mortalitede görülen artış irdelenerek alınması gereken önlemler tartışılacaktır. Gereç ve Yöntem: 01 Ocak 2000 ile 01 Şubat 2004 tarihleri arasında amitriptilin intoksikasyonu nedeni ile yatırılarak takip edilen hastaların dosyaları retrospektif olarak yaş, cinsiyet, semptomlar, klinik bulgular, yoğun bakım ihtiyacı, hastanede kalış süresi ve sonuçlar açısından değerlendirildi. Bulgular: 778 zehirlenme olgusunun 61'i (%7,84) amitriptilinin tek başına ya da diğer ilaçlarında dahil olduğu çoklu ilaç zehirlenmeler oluşturmakta idi. Sadece amitriptilin ile zehirlenen 51 (%6,55) vakanın %56,8'i (n=29) erkek, %43,2'si (n=22) kızdı. Olguların yaşları 13 ay ila 15 yaş arasında idi. Zehirlenme nedenleri arasında % 76,4'ü (n=39) kaza sonucu, %15,3'ü (n=8) intihar amaçlı, %7,8'i (n=4) kötü kullanım vardı. En sık görülen başvuru semptomu sırası ile kusma %29,4 (n=15) ve bilinç değişikliği %23,5 (n=12) idi. Hastaların %27,4'ü (n=14) asemptomatikdi. Hastanede kalış süreleri 1 ila 20 gün (ortalama: 3,6 gün) arasında idi. Hastaların 3'ü takip sırasında kaybedildi, diğerleri şifa ile komplikasyon olmadan taburcu edildi. Sonuç: Amitriptilin zehirlenmeleri sıklığı, çocukluk çağı zehirlenmeleri içinde giderek artmaktadır. Mortalite ve morbidite açısından önemli sonuçlar doğurabileceğinden dolayı koruyucu önlemlerin alınması önem kazanmaktadır. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Çocukluk Çağı Zehirlenmelerinde Artan Tehlike: Amitriptilin